Neuropsychological treatment of ADHD in preschool: Training of executive function - Ramos-Galarza, Carlos (2016)
Preschoolers who have symptoms of impulsivity, hyperactivity and attention deficit manifest alterations in the executive functions: inhibitory control, working memory, monitoring and self-directed speech. It is essential in the preschool classroom to identify children who have difficulty regulating their behavior. The importance of this early detection is the possibility of avoiding a picture of ADHD with greater complexity in the child's future. Training of executive function in children who could present these symptoms has been described as a highly effective strategy. Researches affirm that training of executive function would decrease the likelihood that a child will have ADHD at school age if he had received early attention from preschool. From the clinical experience it has witnessed the evolution of cases of children identified preschool with symptoms of ADHD, and then do a training executive functions for periods of one to two years better, and even at the beginning of schooling have a less severe psychopathology, unlike children who have not received this early intervention. In this paper I will describe the clinical picture of ADHD in initial preschool, the relationship between this disorder and executive function and some strategies in the training of executive functions.